Factors influencing the performance of virtual reality in urban planning: Evidence from a View corridor Virtual Reality project, Beijing. (March 2023) - Jiang, Huaxiong; Geertman, Stan; Zhang, Hao; Zhou, Shangyi
Virtual reality (VR) technologies, as new forms of planning support systems (PSSs), are becoming increasingly vital to planning. However, there is a lack of empirical research on factors influencing VR's supportive role from a user perspective, thus producing barriers to VR's advancement in planning practices. This neglect motivates the focus of this study, in which we adapt relevant PSS theory to build a conceptual framework that examines factors influencing VR performance in an experience-based environment. Empirical data are gathered predominantly through students' experiences with and evaluation of the "Viewing the Western Hills at Yinding Bridge" ( Yinding Guanshan ) VR Project—a VR system developed to optimize the view corridor of Beijing's Western Hills. The results show large variability in factors influencing VR performance. In general, the effects of six factors are significant, including 3D visualization, simulating real-world scenes, user-friendliness, interactivity, inspiring participants' enthusiasm, and inspiring creative thinking. These factors are attributed to the functionality, usability and innovativeness dimensions of VR systems. This study concludes that to realize the supportive and useful role of VR in planning, at minimum, these six factors should be explicitly taken into account.